Torsional Irregularity Control in Irregular Plan RC Buildings through Optimized Shear Wall Placement: A Parametric Study - Bohara, Birendra Kumar; Kunwar, Deepak Bahadur; Kunwar, Bhim (Momentum International Journal of Civil Engineering (MIJCE), 2025)
Irregular buildings, particularly those with L-shaped plans, are more vulnerable during seismic events due to their asymmetric geometry and torsional irregularity. This study investigates the seismic performance of L-shaped reinforced concrete (RC) structures with various shear wall configurations under lateral loading. A total of 12 L-shaped six-story building models were analyzed using ETABS software, applying both Equivalent Static Method (ESM) and Response Spectrum Analysis (RSA) as per IS 1893:2016. The effect of shear wall positioning on fundamental time period, base shear, displacement, torsional irregularity and diaphragm rotation was evaluated. Results showed that shear walls significantly enhance structural performance by reducing displacement, increasing base shear, and controlling torsional behavior when placed effectively. Improper or asymmetric wall placement, however, led to increased torsional amplification and irregular seismic responses. Among all models, those with shear walls aligned along both X and Y directions performed best in terms of seismic resistance. The study highlights the importance of optimal shear wall positioning in irregular RC buildings for enhancing seismic safety and structural efficiency.